2012
DOI: 10.1063/1.4706919
|View full text |Cite
|
Sign up to set email alerts
|

Co-Axial pulse tube for oxygen liquifaction

Abstract: Industrial Research Ltd (IRL) previously developed a single-stage, inline, pulse tube for use with their metallic-diaphragm pressure wave generator (PWG), achieving 45 W of cooling power at 77 K, with 19.5 % of Carnot efficiency (based on the PV input power). This paper describes the conversion of the inline pulse tube to a co-axial configuration that provides a more accessible cold finger. Sage pulse tube simulation software was used to model the modified pulse tube and predicted 105 W of cooling power at 90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The displacer movement is timed in such a way that the bulk of the gas is in the warm end for the compression part of the pressure cycle and in the cold end for the expansion part. Instead of using a mechanically driven displacer as seen in Philips-style Stirling cryocoolers [6], the free-piston Stirling system uses differential gas pressure on the ends of the displacer for movement. The warm side of the displacer is divided into two regions: one region (A2) experiences the supplied pressure wave, http://dx.doi.org/10.1016/j.cryogenics.2016.08.005 0011-2275/Ó 2016 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The displacer movement is timed in such a way that the bulk of the gas is in the warm end for the compression part of the pressure cycle and in the cold end for the expansion part. Instead of using a mechanically driven displacer as seen in Philips-style Stirling cryocoolers [6], the free-piston Stirling system uses differential gas pressure on the ends of the displacer for movement. The warm side of the displacer is divided into two regions: one region (A2) experiences the supplied pressure wave, http://dx.doi.org/10.1016/j.cryogenics.2016.08.005 0011-2275/Ó 2016 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Diaphragm pressure wave generators (DPWG) developed by Industrial Research Ltd, now called Callaghan Innovation [1][2][3][4], have matured over the last decade to become a useful alternative to linear motor pressure wave generators for Stirling and pulse tube cryocoolers [5][6][7][8]. To date, 15 metal diaphragm pressure wave generators have been made and operated with swept volumes from 20 cc to 1000 cc and with 500 W to 30 kW input power, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Linear compressors connected directly to the cold head are a potential candidate to improve this waste energy situation. Caughley et al 2 have shown efficient systems using a high frequency metal diaphragm compressor. This paper describes our work on low frequency linear compressors.…”
Section: Motivationmentioning
confidence: 99%
“…To date, 15 pressure wave generators have been made with swept volumes from 20 cc to 1000 cc [1]- [3]. These have all been coupled to pulse tube [4]- [7] or Stirling [8], [9] cold heads. Two of the DPWGs have each achieved over 7000 hours of operation.…”
Section: Introductionmentioning
confidence: 99%